Embodied Action, Embodied Theory: Understanding the Body in Society - Jacqueline Low; Claudia Malacrida (Societies, 2013)
In 2010 Jacqueline Low was invited to become an editorial board member of the then new online open-access journal Societies. In that same year, Claudia Malacrida was approached to organize a session on the sociology of the body at the 2012 International Sociological Association (ISA) meetings in Buenos Aries. When the call came in 2011 from Societies for editorial board members to propose topics for special issues of the journal, it was a natural and fortuitous timing of events and we undertook to co-edit this special issue based, in part, on papers from the conference. Because of our shared history of writing about social aspects of the body, we were convinced that both the conference and the journal papers would produce interesting and important advancements in a sub-discipline that is making exciting contributions beyond its borders to social theory and empirical sociological work.